2015
DOI: 10.1007/s11096-015-0108-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-adherence in Portugal: findings and implications

Abstract: Background Portugal is currently facing a serious economic and financial crisis, which is dictating some important changes in the health care sector. Some of these measures may potentially influence patients' access to medication and consequently adherence, which will ultimately impact on health status, especially in chronic patients. Aims This study aimed at providing a snapshot of adherence in patients with chronic conditions in Portugal between March and April 2012. Setting Community pharmacy in Portugal. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 36 publications
3
22
0
3
Order By: Relevance
“…A não-adesão secundária diz respeito aos medicamentos não administrados conforme prescritos quando a pessoa já aviou o receituário 51,56 . Sendo assim, a não-adesão secundária está relacionada ao atual comportamento do uso do medicamento, uma vez que o mesmo já foi adquirido 55 . Enquanto já se tem conhecimento das consequências de uma não-adesão secundária, pouco se sabe sobre a não-adesão primária.…”
Section: Tipos De Não-adesãounclassified
“…A não-adesão secundária diz respeito aos medicamentos não administrados conforme prescritos quando a pessoa já aviou o receituário 51,56 . Sendo assim, a não-adesão secundária está relacionada ao atual comportamento do uso do medicamento, uma vez que o mesmo já foi adquirido 55 . Enquanto já se tem conhecimento das consequências de uma não-adesão secundária, pouco se sabe sobre a não-adesão primária.…”
Section: Tipos De Não-adesãounclassified
“…A 2012 patient survey, which included 375 patients sought to provide a snapshot of medication adherence in patients with chronic conditions, found that 22.8% of patients did not purchase prescribed medication, with financial problems cited as one of the main reasons [20]. Another study linked pharmaceutical policy interventions such as harmonizing reimbursement levels and campaigns to promote generics, to utilisation of antipsychotic drugs, found an increase in the use of generic medicines, but also to a decrease in overall sales, consistent with reduced access to medicines [21].…”
Section: Effects Of Health Care Budget Cuts On Health System and Accementioning
confidence: 99%
“…Sample size estimated considered 2 million elderly [12], prevalence of 50% non-adherence to chronic medication [27], assumed normal distribution, a 3% error estimate (d) and 95% confidence level and was targeted at 1067 patients.…”
Section: Population and Samplementioning
confidence: 99%
“…Based on previous research, one anticipated a low participation rate of pharmacies [27]. Therefore, a convenience sample of pharmacies (n = 78) was approached, requesting higher input from them in patient recruitment.…”
Section: Patient Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation